Capital Adequacy and Risk Management in Uzbekistan’s Banking Sector: Trends and Perspectives (The Peerian Journal, 2025)
The adequacy of bank capital remains a cornerstone of financial stability, particularly in emerging economies facing macroeconomic transformation. This paper examines the capital adequacy and risk management practices of Uzbekistan’s commercial banks during 2016–2024, using official statistical data published by the Central Bank of Uzbekistan. The study evaluates trends in capital adequacy, profitability (ROA and ROE), refinancing rate dynamics, and recent regulatory reforms aligned with Basel standards. Findings demonstrate that Uzbekistan’s banking sector has consistently maintained capital adequacy ratios between 14–20%, significantly above the Basel III minimum of 8%. Profitability indicators, however, fluctuated more widely, with ROE dropping to 8.84% in 2016 before recovering. Despite strong capitalization, challenges persist in liquidity management, credit concentration, and risk diversification. The paper concludes with policy recommendations aimed at sustaining resilience while improving efficiency and profitability.